2015
DOI: 10.18203/2320-6012.ijrms20150288
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between nursing care quality, nurse staffing, nurse job satisfaction, nurse practice environment, and burnout: literature review

Abstract: The purpose of this literature review is to explore the relationship between nurse staffing, nurse job satisfaction, nurse practice environment, burnout, and nursing care quality through a consideration of what is meant by perceptions of nursing care quality. Different people define nursing care quality in many ways. It is complex, multi-faceted and multi-dimensional, and attempts to assess, monitor, evaluate and improve nursing care quality have evolved over a number of years. Of particular interest is the wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
55
0
10

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(65 citation statements)
references
References 52 publications
0
55
0
10
Order By: Relevance
“…; Koy et al. ). This is serious considering that nursing occupies 90% of all healthcare services globally and QNC is one of the main components of healthcare quality (Nilsson et al.…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations
“…; Koy et al. ). This is serious considering that nursing occupies 90% of all healthcare services globally and QNC is one of the main components of healthcare quality (Nilsson et al.…”
Section: Introductionmentioning
confidence: 97%
“…; Koy et al. ). Another major component of QNC relates to an appropriate patient‐to‐nurse ratio, but there are significant fluctuations in nurse–patient ratios across countries globally, as depicted on the World Health Organization (WHO) Global Health Observatory website (WHO ).…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…How colleagues work together is fundamental to [deleted -the experience in the] creating a supportive workplace culture, and feeling supported in the workplace is important for resilience (Koy et al 2015). Senior staff members with managerial responsibility might have more of a sense of how their relationships with colleagues can contribute to the resilience of others because they may be called upon to support colleagues in difficulty and the organisational structure reinforces their responsibilities in this regard.…”
Section: Establishing a Supportive Workplace Culturementioning
confidence: 99%
“…A total of 27% stated that they left because of disillusionment with the level of care offered to patients . This is reflected by Koy et al's (2015) literature review, which identified that job dissatisfaction and burnout contributed to the 'intention [of nurses] to leave, absenteeism, turnover, and adverse outcomes in hospital care.' They also highlight how nurse burnout is not only detrimental for nurses, but has also been associated with lower levels of patient satisfaction and nursing care quality (Koy et al 2015).…”
Section: Introductionmentioning
confidence: 99%